Medicolegal Death Investigation and Hospital Patient Safety and Quality Outcomes: A Naturally Synergistic Collaboration. Issue 4 (October 2016) - Drake, Stacy A.; Harper, Sherhonda; Wolf, Dwayne A.
Abstract : ABSTRACT: The role of medicolegal death investigation (MLDI) systems in the assessment of violent deaths (e.g., gunshots, stab wounds, car crashes) is well known. However, the role of MLDI systems in informing healthcare agencies about potential patient safety and quality improvement activities is less understood and thus the main focus of this article. In this article we describes-one agency's initiatives to identify decedents whose circumstances or cause of death had potential relevance for patient safety and quality outcomes and to communicate those findings to acute care hospitals where the decedents were previously treated. We also describes the evaluation of this communication process and provide preliminary outcomes of these efforts.